COMMEMORATIVE PRACTICES IN THE PUBLIC AND POLITICAL LIFE OF THE KABARDINO-BALKAR REPUBLIC - ATLASKIROV, A.R. (Kavkazologiya, 2020)
One of the most significant places in the social and political life of modern Russia is occupied by the politics of historical memory. After the unsuccessful attempts of the "new" Russian elite in the 90s of the 20th century to integrate the country into the culture and history of Europe, having reshaped the country on the model of Western countries, the demand for an independent path of development has matured in society. In the high echelons of power, there is an awareness of the need to consolidate society by promoting among the masses the idea of a single historical destiny of the country's peoples. Under these conditions, in all regions of the country, including Kabardino-Balkaria, the activities of state and public organizations have intensified in the direction of creating new and popularizing existing all-Russian commemorative practices designed to unite the country around a common historical memory. In the course of the study, the commemorative practices of Kabardino-Balkaria were divided into several main groups: national, republican, ethnic, religious, and commemoration of global culture. It was also revealed that globalization processes have a significant impact on the formation of commemorative practices in the republic especially among the youth. The greatest conflict potential is possessed by the ethno-national commemorative practices connected with historical experience of the titular peoples of Kabardino-Balkaria.